2016
DOI: 10.1007/s10926-016-9674-x
|View full text |Cite
|
Sign up to set email alerts
|

Limitations to Work-Related Functioning of People with Persistent “Medically Unexplained” Physical Symptoms: A Modified Delphi Study Among Physicians

Abstract: Purpose The purpose of this study was to obtain consensus among physicians of several medical specialties on the level of limitations to work-related functioning of people with persistent “medically unexplained” physical symptoms (PPS). Methods A modified Delphi study was conducted with 15 physicians of five different medical specialties. The study involved two email rounds and one meeting. In each round, the physicians prioritized the level of limitations in 78 work-related functioning items for four differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…The nominal group technique was used to structure the meeting to explore differences between individual labour experts and caseworkers in their opinion about RTW barriers and interventions and to reach consensus among the participants by group discussions [ 13 ]. Earlier studies have successfully used the combination of the Delphi technique and nominal group technique [ 14 , 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…The nominal group technique was used to structure the meeting to explore differences between individual labour experts and caseworkers in their opinion about RTW barriers and interventions and to reach consensus among the participants by group discussions [ 13 ]. Earlier studies have successfully used the combination of the Delphi technique and nominal group technique [ 14 , 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…First, in different countries the concept is assessed differently [2]; various methods are used to aid in assessment, the most common being clinical tests, functional capacity evaluations, and psychological tests. Second, high inter-doctor disagreements have been found on the outcome of assessing inability to work fulltime, questioning the credibility of the current assessment procedures [4][5][6]. In a previous study we found that, although 10 out of 13 countries use formal rules to assess inability to work, in the Netherlands only a professional guideline is used [2].…”
Section: Introductionmentioning
confidence: 95%
“…Generally, the diagnosis is an important predictor of certified sick leave and symptom diagnoses imply shorter sick leave (Starzmann et al, 2015). Deciding the level of work-related limitations to functioning may be especially difficult for patients with symptom diagnoses and physicians are divided in their initial assessments of these patients (although research suggests the potential for reaching a broader consensus) (Weerdesteijn et al, 2017).…”
Section: Does Diagnosis Matter?mentioning
confidence: 99%